Adipose tissue induces trained innate immunity in patients with obesity. (14th October 2021) - Van Tuijl, J; Vreeken, D; Broeders, W; Stienstra, R; Joosten, L A B; Netea, M G; Hazebroek, E J; Kiliaan, A J; Bekkering, S; Riksen, N P
Abstract: Introduction: Obesity is the most prevalent modifiable risk factor for atherosclerotic cardiovascular disease and is characterized as a chronic inflammatory disease. Cells of the innate immune system, especially monocytes and macrophages, play a pivotal role in the various stages of atherosclerosis, although it still remains elusive why the strong inflammatory response persists in time. We recently showed that cells of the innate immune system, such as monocytes, can adopt a long-term immunological memory. Upon brief stimulation with atherogenic stimuli, monocytes demonstrate an enhanced long-term pro-inflammatory and pro-atherogenic phenotype. This is termed trained immunity and is mediated via epigenetic and metabolic reprogramming. The clinical relevance of these findings was verified in patients with symptomatic atherosclerosis, in which circulating monocytes showed a trained immune phenotype. Purpose: As various adipose tissue-related particles, including pro-inflammatory cytokines and fatty acids, are capable of inducing trained immunity in vitro, we hypothesized that adipose tissue from obese subjects might induce training in peripheral monocytes, thereby contributing to the increased risk of atherosclerotic CVD in these patients. In line with this hypothesis, it is unclear whether chronic inflammation sustains after a previous period of obesity despite significant weight loss. Methods: We obtained blood from 25 patients with obesity before and 6 months after bariatric surgery. Monocyte subsets and activation phenotype were studied using flow cytometry. Cytokine production capacity of isolated PBMCs was studied after ex vivo stimulation with several infectious and metabolic stimuli and we characterized isolated monocytes using transcriptomics. Next, we obtained visceral (VAT) and subcutaneous adipose tissue (SAT) biopsies from 10 patients. Using our established in vitro model for trained immunity, we co-incubated healthy human monocytes with the adipose tissue biopsies for 24 hours in a trans-well set-up. After 24 hours, the adipose tissue was removed and monocytes were rested. On day 6, the cells were re-stimulated for 24 hours with a second stimulus and cytokine production and the transcriptome of the macrophages was analyzed. Results: Both SAT and VAT obtained from patients with obesity can induce a long-term memory in healthy human monocytes, as demonstrated by an increased cytokine production capacity 6 days after co-incubation. Interestingly, VAT induced a higher cytokine response compared to SAT. Analysis of the inflammatory phenotype of peripheral cells before and after bariatric surgery is currently ongoing. Conclusions: Adipose tissue-secreted metabolites, particularly secreted by VAT, have the potential to induce persistent innate immune cell activation. Our further analyses will show whether the secretion of these molecules and the activation of the innate immune system persists upon weight loss. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Dutch Heart Foundation